Biodiversity and trophic structure of invertebrate assemblages associated with understorey red algae in a Laminaria digitata bed. Issue 5 (27th May 2016) - Schaal, Gauthier; Leclerc, Jean-Charles; Droual, Gabin; Leroux, Cedric; Riera, Pascal
ABSTRACT: Although the composition of invertebrate assemblages associated with kelps has motivated several studies in the recent past, little is known about assemblages associated with smaller, understorey macroalgae in these ecosystems. Here, the composition of invertebrate assemblages living within understorey macroalgae of a kelp ( Laminaria digitata ) forest has been studied over two sampling dates, and the structure of the food web investigated using stable isotopes. A total of 145 species of mobile fauna, mainly amphipods and gastropods, were identified. Although differences were date-dependent, we showed that the three species considered ( Palmaria palmata, Mastocarpus stellatus, Ellisolandia elongata ) sheltered different associated assemblages, including high host-specificity, which suggests that the animal diversity associated with rocky shores is enhanced by a high algal diversity. Overall, a dominance of gastropods was observed for the two-dimensional, leaf-like P. palmata, while the three-dimensionally structured species ( M. stellatus, E. elongata ) were characterized by a dominance of amphipods. Stable isotopes highlighted different trophic structures; E. elongata -associated assemblages were most likely relying on a dominant food source, sediment organic matter, while other assemblages were based on a wider diversity of food sources (algae, sediment, suspended organic matter). Our results illustrate the need to consider the microhabitats formed by understorey macroalgae in order to thoroughly assess the diversity and understand the functioning of coastal rocky ecosystems.